Molecular Engineering toward High‐Crystallinity Yet High‐Surface‐Area Porous Carbon Nanosheets for Enhanced Electrocatalytic Oxygen Reduction. Issue 3 (16th November 2021) - Chen, Yongqi; Huang, Junlong; Chen, Zirun; Shi, Chenguang; Yang, Haozhen; Tang, Youchen; Cen, Zongheng; Liu, Shaohong; Fu, Ruowen; Wu, Dingcai
Abstract: Carbon‐based nanomaterials have been regarded as promising non‐noble metal catalysts for renewable energy conversion system (e.g., fuel cells and metal–air batteries). In general, graphitic skeleton and porous structure are both critical for the performances of carbon‐based catalysts. However, the pursuit of high surface area while maintaining high graphitization degree remains an arduous challenge because of the trade‐off relationship between these two key characteristics. Herein, a simple yet efficient approach is demonstrated to fabricate a class of 2D N‐doped graphitized porous carbon nanosheets (GPCNSs) featuring both high crystallinity and high specific surface area by utilizing amine aromatic organoalkoxysilane as an all‐in‐one precursor and FeCl3 ·6H2 O as an active salt template. The highly porous structure of the as‐obtained GPCNSs is mainly attributed to the alkoxysilane‐derived SiO x nanodomains that function as micro/mesopore templates; meanwhile, the highly crystalline graphitic skeleton is synergistically contributed by the aromatic nucleus of the precursor and FeCl3 ·6H2 O. The unusual integration of graphitic skeleton with porous structure endows GPCNSs with superior catalytic activity and long‐term stability when used as electrocatalysts for oxygen reduction reaction and Zn–air batteries. These findings will shed new light on the facile fabrication of highly porous carbon materials with desired graphitic structure for numerous applications. Abstract : 2D N‐doped graphitized porous carbon nanosheets (GPCNSs) featuring both high crystallinity and high specific surface area are prepared by molecular engineering. The unusual integration of graphitic skeleton with porous structure endows GPCNSs with superior catalytic activity and long‐term stability when used as electrocatalysts for oxygen reduction reaction and Zn–air batteries.